The Sign 4 Little Talkers Intervention to Improve Listening, Understanding, Speaking, and Behavior in Hearing Preschool Children: Outcome Evaluation - Davidson, Rosemary; Randhawa, Gurch (JMIR Publications, 2020)
BackgroundGaining age-appropriate proficiency in speech and language in the early years is crucial to later life chances; however, a significant proportion of children fail to meet the expected standards in these early years outcomes when they start school. Factors influencing the development of language and communication include low income, gender, and having English as an additional language (EAL). ObjectiveThis study aimed to determine whether the Sign 4 Little Talkers (S4LT) program improves key developmental outcomes in hearing preschool children. S4LT was developed to address gaps in the attainment of vocabulary and communication skills in preschool children, identified through routine monitoring of outcomes in early years. Signs were adapted and incorporated into storybooks to improve vocabulary, communication, and behavior in hearing children. MethodsAn evaluation of S4LT was conducted to measure key outcomes pre- and postintervention in 8 early years settings in Luton, United Kingdom. A total of 118 preschool children were tested in 4 early years outcomes domains-listening, speaking, understanding, and managing feelings and behavior-as well as Leuven well-being scales and the number of key words understood and spoken. ResultsStatistically significant results were found for all measures tested: words spoken (P<.001) and understood (P<.001), speaking (P<.001), managing feelings and behavior (P<.001), understanding (P<.001), listening and attention (P<.001), and well-being (P<.001). Approximately two-thirds of the children made expected or good progress, often progressing multiple steps in educational attainment after being assessed as developmentally behind at baseline. ConclusionsThe findings reported here suggest that S4LT may help children to catch up with their peers at a crucial stage in development and become school ready by improving their command of language and communication as well as learning social skills. Our analysis also highlights specific groups of children who are not responding as well as expected, namely boys with EAL, and who require additional, tailored support.